Molecular identification of antelope horn by melting curve analysis. (1st November 2016) - Tong, Yuru; Jiang, Chao; Yuan, Yuan; Jin, Yan; Cui, Zhan-hu; Huang, Luqi
Abstract: Antelope horn is a valuable Chinese traditional medicine and widely used in clinic. However, with the deterioration of antelope's living environment and a lot of killing, the saiga population begins falling and in some places plummet. Since the increasing demand of this expensive and good bioactive medicine, the horn of artiodactyla animals is often used as the antelope horn. The adulterated or impostor not only cause damage to clinical medicine but also affect the antelope resources protection and sustainable development. Here, in order to establish a melting curve analysis (MCA) method to distinguish the antelope horn from other animal horns and identify the decoction pieces and Chinese patent medicine in a fast and easy way, animal horns and its decoction pieces, Chinese patent medicines were collected from the market and the DNA of all the collected samples were extracted. The melting curve of two universal fragments ( CO I and Cyt b) was scanned and Cyt b was selected as feasibility fragment for identifying authentic antelope horn from eight adulterant animal horns. After optimizing the condition for MCA, inspecting the precision and the replication of the method, a reference melting curve modern was established and we performed MCA on the antelope horns, fakes, and adulterants on a 1:1 mix, decoction pieces, and Chinese patent medicine. Thus, this study provides fast and easy methods so that MCA can detect the truth, fakes, and adulterations of antelope horns.